2018
DOI: 10.1089/neu.2017.5092
|View full text |Cite
|
Sign up to set email alerts
|

Rolipram-Loaded Polymeric Micelle Nanoparticle Reduces Secondary Injury after Rat Compression Spinal Cord Injury

Abstract: Among the complex pathophysiological events following spinal cord injury (SCI), one of the most important molecular level consequences is a dramatic reduction in neuronal cyclic adenosine monophosphate (cAMP) levels. Many studies shown that rolipram (Rm), a phosphodiesterase IV inhibitor, can protect against secondary cell death, reduce inflammatory cytokine levels and immune cell infiltration, and increase white matter sparing and functional improvement. Previously, we developed a polymeric micelle nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…To validate the role of AMPK‐dependent induction of autophagy in EPO's neuroprotection, we performed the in vitro study. PC12 cells (an extensively used neuronal cell line) were cultured in hypoxia condition as an in vitro neuronal injury model. CCK8 assay showed that hypoxia significantly reduced the cell viability, whereas pretreatment with EPO for 2 hours prior to hypoxia attenuated this decrease of cell viability (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…To validate the role of AMPK‐dependent induction of autophagy in EPO's neuroprotection, we performed the in vitro study. PC12 cells (an extensively used neuronal cell line) were cultured in hypoxia condition as an in vitro neuronal injury model. CCK8 assay showed that hypoxia significantly reduced the cell viability, whereas pretreatment with EPO for 2 hours prior to hypoxia attenuated this decrease of cell viability (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these approaches are for direct injection (e.g., hydrogels, nanoparticles, nanofibers, etc.) at the lesion site but few studies have also reported the use of nanomaterials for drug delivery via intravenous injection but were given immediately or within a very short time window post-injury [26,27]. As such, there is no systematic study aimed at analyzing the effect of different parameters that are critical for localization of NPs at the lesion site under clinically relevant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia treatment was performed in AGE1.HN and PC12 cell lines for simulating SCI in vitro, as previously reported [14,15]. Oxygenglucose deprivation (OGD) was performed upon the above cells for hypoxia treatment in accordance with a previous study [16].…”
Section: Western Blottingmentioning
confidence: 99%